Brain Fluorine-18 Fluorodeoxyglucose Imaging with Dual-Head Coincidence Gamma Camera:Comparison with Dedicated Ring-Detector PositronEmission Tomography - Fukuchi, Kazuki (AJNR Am J Neuroradiol, 2000)
BACKGROUND AND PURPOSE: Dual-head coincidence gamma camera (DHC) imaging has been proposed as an alternative to dedicated ring-detector positron emission tomography (dr-PET) for clinical fluorodeoxyglucose (FDG) studies. The purpose of this investigation was to assess the quality of DHC images in FDG studies of the human brain. METHODS: Seven healthy volunteers and 12 patients with various cerebral disorders underwent consecutive brain dr-PET and DHC with FDG. All sets of images were compared semiquantitatively using regions of interest. RESULTS: Cortical count ratios to the cerebellum on DHC and dr-PET images did not differ significantly among the volunteers, except in the superior frontal cortex and thalamus. In all studies including those of cerebral disorders, the mean cortical-to-cerebellar ratios of DHC and dr-PET images correlated closely. CONCLUSION: FDG imaging with DHC delineated the metabolic distribution of glucose in the brain as well as dr-PET did, except in the superior frontal cortex and thalamus. Therefore, DHC may be a dedicated cost-effective means of detecting metabolic abnormalities in the brain.